SCROLLING INTO SLEEPLESSNESS: HOW INSOMNIA MEDIATES THE IMPACT OF SOCIAL MEDIA ON WELLBEING-WITH A LIFELINE FROM FAMILY SUPPORT (The Research of Medical Science Review, 2025)
Background: Excessive social media usage disrupts sleep, leading to insomnia, which negatively impacts psychological well-being. Insomnia heightens stress, anxiety, and depressive symptoms, worsening mental health. However, strong family support can buffer these effects, promoting emotional stability. Understanding these relationships is crucial for improving psychological well-being. Purpose: Current study is conducted to explore the interplay of insomnia between the relationships of social media on the psychological wellbeing of an individual. Specifically, it examines how family support hinders the impacts of social media usage and insomnia on the psychological wellbeing. Methodology: The data was collected from 378 employees of Pakistan using Convenient Non –Probability Sampling Technique. Data was analyzed using SPSS and Smart PLS. Findings: Using a sturdy analytical framework, the findings reveal that Social media usage significantly increases insomnia. Elevated insomnia, in turn, negatively impacts psychological wellbeing. Mediation analysis endorses that insomnia mediates the relationship between social media usage and psychological wellbeing. Additionally, Family Support weakens the relationship between insomnia and psychological wellbeing. Implications: These findings highlight the crucial roles of insomnia and social media in shaping psychological wellbeing, along with the buffering effects of family support, providing valuable insights for public health strategies and communication interventions.